P‐23: A Subjective Method for Evaluating Foveated Image Quality in HMDs. Issue 1 (25th September 2020) - Thirumalai, Vijayaraghavan; Ribera, Javier; Xiang, Jie; Zhang, Junbin; Azimi, Maryam; Kamali, Jalil; Nasiopoulos, Panos
Abstract : Analyzing the perceptual image quality rendered on a head‐mounted display (HMD) is of primary importance to provide a flawless visual quality to VR headset users. In this paper, we propose a new subjective testing method to evaluate the quality of foveated images in HMDs. The images we use are coded by progressively increasing the compression ratio from the fixation point to the periphery. Our method is based on a standardized flickering paradigm which temporally interleaves the original and reconstructed images to make the differences more prominent. Results indicate that observers can identify more visual impairments near the fixation point than in periphery. This new subjective testing approach is, therefore, effective in assessing barely visible image artifacts of foveated imaging in HMDs.